Investigation of the Effect of Harmonics Caused by Transformer-Induced Nonlinear Loads on Electrical Energy - Rustemli, Sabir; Sezgin, Nejdet; Coskun, Bilal; Sahin, Gokhan (Scipedia S L, 2025)
In this study, distribution transformers in the Mugs Alparslan University campus are analyzed in order to minimize energy losses due to harmonics in the electrical network. Current and voltage harmonics, which are the power quality problems of these transformers, are analyzed. The power quality of different transformers in Mugs Alparslan University was measured with a Chauvin Arnoux CA:8331 energy analyzer. Three-phase nonlinear load models were created using current harmonic values in the Matlab/Simulink environment. A parallel active power filter is designed in the Matlab/Simulink environment to eliminate current harmonics. The performance of the parallel active power filter is analyzed for each transformer. As a result, the total harmonic distortion (THDI) ratio for the current decreased from 6.78% to 1.38% in fast Fourier transform analyses after the parallel active power filter was activated in the first transformer. Similarly, the THDI ratio decreased from 5.1% to 2.19% in the second transformer, from 4.5% to 1.39% in the third transformer, and from 5.63% to 1.36% in the fourth transformer.
Keywords: Harmonics; energy quality; active parallel power filter; Matlab/Simulink